The higher education personal tutor's and advisor's companion : translating theory into practice to improve student success - Lochtie, Dave; Stork, Andrew; Walker, Ben (Ben W.); McIntosh, Emily; Thomas, Liz (Elizabeth) (Higher education., 2022)
Stories of practice, with critical insights, from a range of higher education practitioners and settings providing professional learning and development for personal tutors and academic advisors.